Rethinking active learning program for primary English teachers through connoisseurship technique - Nippita Kulachit; Prasart Nuangchalerm (Journal of Education and Learning (EduLearn), 2021)
From the importance of Englishin world of internationally communicated,  the problems of learning management in each area seems to be differenced, language and culture are needed for recognizing, active learning is called for  effectiveness instruction, and primary English teachers need to prepared in modern classroom. This research employed evaluative research to employ active learning for primary English teachers through professional program. Data were collected by setting a connoisseurship technique. Seven experts are appointed and read carefully a tentative program for primary English teachers. The connoisseurship technique allowed all experts share their experiences and ideas to promote active learning in freely. Video recording and note taking were recorded during the validation activity. Active learning program for primary English teachers is approved before implementation in different school contexts. The uncertainty situations, COVID-19 pandemic may be affected to schooling, teachers have to redesign lesson. The implementation though active online learning is needed to discuss and rethinking how it be effectively in authentic classroom.